Solve for t (7t-2)-(-3t+1)=-3(1-3t)

Math
(7t-2)-(-3t+1)=-3(1-3t)
Simplify (7t-2)-(-3t+1).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
7t-2-(-3t)-1⋅1=-3(1-3t)
Multiply -3 by -1.
7t-2+3t-1⋅1=-3(1-3t)
Multiply -1 by 1.
7t-2+3t-1=-3(1-3t)
7t-2+3t-1=-3(1-3t)
Simplify by adding terms.
Tap for more steps…
Add 7t and 3t.
10t-2-1=-3(1-3t)
Subtract 1 from -2.
10t-3=-3(1-3t)
10t-3=-3(1-3t)
10t-3=-3(1-3t)
Simplify -3(1-3t).
Tap for more steps…
Apply the distributive property.
10t-3=-3⋅1-3(-3t)
Multiply.
Tap for more steps…
Multiply -3 by 1.
10t-3=-3-3(-3t)
Multiply -3 by -3.
10t-3=-3+9t
10t-3=-3+9t
10t-3=-3+9t
Move all terms containing t to the left side of the equation.
Tap for more steps…
Subtract 9t from both sides of the equation.
10t-3-9t=-3
Subtract 9t from 10t.
t-3=-3
t-3=-3
Move all terms not containing t to the right side of the equation.
Tap for more steps…
Add 3 to both sides of the equation.
t=-3+3
Add -3 and 3.
t=0
t=0
Solve for t (7t-2)-(-3t+1)=-3(1-3t)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top